Clinical efficacy, safety and tolerance of the Kerawort (imiquimod) cream used for treatment of anogenital warts - M. R. Rakhmatulina; A. A. Kubanov; A. V. Samtsov; A. V. Sukharev; O. I. Bondar; A. V. Semenenko (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal of the study. To assess the efficacy and safety of Kerawort (Imiquimod, 5% cream for topical administration) vs. placebo used for treatment of anogenital warts. Methods and materials. The single-blind comparative placebo-controlled study involved 90 patients (44 female and 46 male) with anogenital warts. The patients were randomized into two groups: the main group (n = 45) receiving treatment with Kerawort (Imiquimod, 5% cream) and the control group (n = 45) receiving placebo. The diagnosis was confirmed by the identification of human papillomavirus by the polymerase chain reaction method. The patients received treatment three times a week until clinical signs disappeared but for not more than 16 weeks. Results. In 95.6% of patients from the main group and 8.9% of patients from the control group, anogenital warts disappeared completely or the quantity/area of pathological eruptions reduced at least by 70% as compared to the baseline. No relapses occurred during the treatment and follow-up period (28 days after the completion of treatment) in patients from the main group. An increase in the size and/or area of anogenital warts and/or development of new eruptions on the skin and mucous membrane of the genitals were recorded in 11.1% of patients from the control group. No serious adverse events were revealed during the study. Conclusion. Higher efficacy (р < 0.0000001) and comparable safety of Kerawort (Imiquimod, 5% cream for topical administration) used for treatment of anogenital warts vs. placebo were reliably established.